2020
DOI: 10.1007/s42452-020-03478-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of quaternary groundwater under the influence of anthropogenic activities in the low-income neighbourhoods of the Treichville municipality (Abidjan, Côte d’Ivoire)

Abstract: This study aims to assess the groundwater quality and the origin of water mineralization in an environment with high anthropogenic pressure in the municipality of Treichville. Twenty-one water samples were analysed to determine the quality. Kruskal-Wallis nonparametric test, Mann-Whitney test, Kohonen algorithm, and water table building were used to determine the factors influencing the mineralization. The results showed that the well's water contains chemical and bacteriological elements whose concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…For instance, one of the studies reported EC values ranging from 781 to 2810 μS/cm, with a mean value of 1801.7 μS/cm [19]. Another study indicated that EC values in groundwater varied from 63 to 3819 μS/cm, with the majority of wells consisting of freshwater (< 1000 μS/cm) during rainy seasons [21]. It has been stressed that in order to assure sustainable agricultural activities, the treated wastewater should meet the given quality standards by involving a close monitoring just not on the EC but also at the other variables including pH, TDS, BOD, COD, nutrient contents, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one of the studies reported EC values ranging from 781 to 2810 μS/cm, with a mean value of 1801.7 μS/cm [19]. Another study indicated that EC values in groundwater varied from 63 to 3819 μS/cm, with the majority of wells consisting of freshwater (< 1000 μS/cm) during rainy seasons [21]. It has been stressed that in order to assure sustainable agricultural activities, the treated wastewater should meet the given quality standards by involving a close monitoring just not on the EC but also at the other variables including pH, TDS, BOD, COD, nutrient contents, etc.…”
Section: Introductionmentioning
confidence: 99%